ChemInform Abstract: Phosphathiahelicenes: Synthesis and Uses in Enantioselective Gold Catalysis. Issue 12 (March 2015) - Aillard, Paul; Voituriez, Arnaud; Dova, Davide; Cauteruccio, Silvia; Licandro, Emanuela; Marinetti, Angela
Abstract An enantiopure phosphathiahelicene is prepared and successfully applied as the catalyst for the enantioselective cycloisomerization of N‐tethered enynes.